MACHINE LEARNING TO PREDICTE CANCER - ESTEPA RODOLFO SANTIAGO JOSE; KINSEY CHRISTOPHER MICHAEL; STEVENSON CHRISTOPHER S; VOSKOW JR GEOFF (2023)
Disclosed herein are methods for determining a subject level risk of metastatic cancer comprising training and/or deploying a model to determine: 1) a lymph node level risk implied by an individual lymph node; and/or 2) a lymph node-dependent subject level risk. Thus, the method may identify high or low risk patients with sarcoidosis and optionally enable guidance of intervention in cancer patients, for example via treatment. 本文公开了用于确定转移癌的受试者水平风险的方法，其包括训练和/或部署模型以确定：1)个体淋巴结累及的淋巴结水平风险；以及/或者2)淋巴结累及的受试者水平风险。因此，该方法可识别具有结节病的高风险或低风险的患者，并且任选地使得能够例如经由治疗来指导癌症患者的干预。